Apoptosis in Blastocystis spp. is related to subtype - Dhurga, D.B.; Suresh, K.G.; Tan, T.C.; Chandramathi, S. (2012)
Previous studies have shown that apoptosis-like features are observed in Blastocystis spp., an intestinal protozoan parasite, when exposed to the cytotoxic drug metronidazole (MTZ). This study reports that among the four subtypes of Blastocystis spp. investigated for rate of apoptosis when treated with MTZ, subtype 3 showed the highest significant increase after 72 h of in vitro culture when treated with MTZ at 0.1 mg/ml (79; p<0.01) and 0.0001 mg/ml (89; p<0.001). The close correlation between viable cells and apoptotic cells for both dosages implies that the pathogenic potential of these isolates has been enhanced when treated with MTZ. This suggests that there is a mechanism in Blastocystis spp. that actually regulates the apoptotic process to produce higher number of viable cells when treated. Apoptosis may not just be programmed cell death but instead a mechanism to increase the number of viable cells to ensure survival during stressed conditions. The findings of the present study have an important contribution to influence chemotherapeutic approaches when developing drugs against the emerging Blastocystis spp. infections. (C) 2012 Royal Society of Tropical Medicine and Hygiene. Published by Elsevier Ltd. All rights reserved.